Uma metodologia para a determinação de sistemas de produção agrícola - Coelho de Alvarenga, Sonia; Batista de Oliveira, Evonir (Revista Ceres, 2025)
This study presents a methodology for empirical determination «ex-post» of production systems in agriculture. The framework consists in classifying the systems according to the presence of basic elements defining macrovariables. The methodology was used in three separate studies concerning beef and dairy cattle. The results achieved were highly satisfactory both with respect to the methodology and prescriptive applications of the recommendations that were drawn from the results.